Novel therapeutic approaches for steroid-resistant nephrotic syndrome in paediatric patients: a comprehensive review - Kumar, Rajan; Kumar, Santosh; Kumar, Deepak; Ansari, Ehtesham (International Journal of Contemporary Pediatrics, 2024)
Steroid-resistant nephrotic syndrome poses a significant therapeutic challenge in paediatric nephrology. Previously exact cause of steroid-resistant nephrotic syndrome was mostly unknown. Recently, advancements in diagnostic intervention, they are found to be a heterogeneous entity having an immune basis and genetic aetiology. With a better understanding of the pathogenesis of SRNS, leading to the development of novel therapeutic strategies. Novel therapeutic options include extracorporeal therapy, monoclonal antibodies, stem cell therapy, ACTH and galactose. The aim of this study was to provide an overview of emerging therapies for SRNS in paediatric populations.